Exploring customers' responses to online service failure and recovery strategies during Covid‐19 pandemic: An actor–network theory perspective. Issue 9 (18th June 2021) - Ozuem, Wilson; Ranfagni, Silvia; Willis, Michelle; Rovai, Serena; Howell, Kerry
Abstract: While the debate on online service failure and recovery strategies has been given considerable attention in the marketing and information systems literature, the evolving Covid‐19 pandemic has brought about new challenges both theoretically and empirically in the consumption landscape. To fully understand customers' responses to service failure during a crisis we asked 70 millennials from three European Countries—Italy, France, and the UK—to describe their responses to service failure during the Covid‐19 pandemic (30 completed a 4‐week diary and 40 completed a 4‐week qualitative survey). Drawing on phenomenological, constructivist, and hermeneutical approaches, and utilizing an actor–network theory perspective, the current study proposes a new framework for understanding customers' responses to online service failure and recovery strategies during the Covid‐19 pandemic. Conclusions highlight implications for theory, policy, and management practice through extending comprehensions of service failure recovery processes by examining how marketing policies generate different social impacts during a crisis situation which facilitate the achievement of customer satisfaction and positive outcomes.